Increasing Donations and Improving Donor Experiences: Lessons From Decision Science. (October 2015) - Oppenheimer, Daniel M.
Giving to charity not only helps fund programs that are beneficial to society but also reliably increases the well-being of donors. However, not all donations are equally effective at improving donor happiness. This article reviews the research from psychology and behavioral economics and identifies several key factors for optimizing donor experiences. These lessons can be used to design charitable appeals that are highly effective and that create conditions that make charitable giving more rewarding to donors, which increases the likelihood that they will donate again.